(AT)n is an interspersed repeat in the Xenopus genome. - Greaves, D R (1985)
We have observed (AT)34 and (AT)23 tracts close to the coding sequences of the Xenopus laevis tadpole alpha T1 and adult beta 1 globin genes, respectively. We show that (AT)n sequences are found as interspersed repeats within the Xenopus globin and histone gene loci. Using (AT)n co-polymer in filter hybridisation experiments we estimate that there are 10(4) (AT)n tracts per haploid Xenopus genome. Hybridisation to genomic blots of DNA from yeast, slime mold, trypanosome, fruit fly, salmon, chicken, rat, human, crab and Xenopus species shows that strictly alternating AT of sufficient length to hybridise appears to be most abundant in Xenopus and crab genomes. We show that the specificity of the co-polymer probe for strictly alternating AT is, however, dependent on the length of the probe. Hybridisation experiments using (TG)n copolymer suggest that this highly conserved repeat is found as clustered repeats in the Xenopus genome in contrast to other eukaryotic genomes so far studied.